Megavirus baoshanense Mb0671 modulates host translation and increases viral fitness - Bian, Wenya; Yang, Jie; Xia, Yucheng; Li, Yun; Cheng, Yanjin; Wu, Yuchen; Gan, Jianhua; Zhong, Jiang (Frontiers in Microbiology, 2025)
Amoeba giant viruses encode many translation-related proteins, but the function of these proteins remains obscure. In the current work, we studied the potential eukaryotic translation initiation factor 4A (eIF4A, Mb0671) encoded by Megavirus baoshanense, a member of the family Mimiviridae. The protein was shown to possesse ATPase activity and RNA-binding capacity, localize in the cytoplasm of infected cells, and present in mature virions. Interactome analysis showed that Mb0671 interacted primarily with ribosomal proteins and translation-related proteins. Specifically, Mb0671 was found to interact indirectly with host eIF4A, suggesting that it was associated with the translation apparatus. Proteomic analysis revealed that the protein profile of Acanthamoeba castellanii cells stably expressing Mb0671 was altered significantly compared to wild-type cells. The cellular proteins that were significantly upregulated included those in the pathways of spliceosome, amino acids biosynthesis, ribosome biogenesis, vesicular transportation, mTOR signaling pathway, etc. Both Mb0671 overexpression or siRNA-mediated reduction of its expression level significantly affected the synthesis of viral proteins. Furthermore, overexpressing Mb0671 accelerated cell growth and virus replication, whereas reduction of Mb0671 expression by siRNA delayed virus replication. These results suggested that Mb0671 altered cellular translation, possibly through its association with the host translation machinery, and played an important role in enhancing virus adaptability.